Koniec męskości, albo Wiedźmina opisanie - Matuszek, Dawid (Śląskie Studia Polonistyczne, 2016)
In his article the author sketches a portrait of Geralt of Rivia, a title character of Andrzej Sapkowski’s Witcher series aw well as a video game The Witcher 3: Wild Hunt, while at the same time tracing the work of deconstruction inscribed in the figure of the hero. Most significantly, it is Geralt’s gender identity that becomes subject to deconstruction; a model of heroic, fatherly, withdrawn masculinity becomes subverted and unseamed – on the one hand by female corporality; on the other, by female politics – which results in questioning and rejecting the so far dominant model in favour of subjectivity suspended between femininity and masculinity (and their other variants).